IMPLEMENTASI SISTEM FULLDAY SCHOOL DI SDS ISLAM TERPADU SULTHONIYAH SAMBAS TAHUN AJARAN 2024-2025 - Almiati Almiati; Aslan Aslan; Eliyah Eliyah (JIP: Jurnal Ilmu Pendidikan, 2025)
The objectives of this research are to describe: 1) the full-day school system at SDS IT Sulthoniyah Sambas for the 2024-2025 academic year; 2) the challenges and opportunities of the full-day school at SDS IT Sulthoniyah Sambas for the 2024-2025 academic year; and 3) the implications of the full-day school system on the psychological development of students at SDS IT Sulthoniyah Sambas for the 2024-2025 academic year. This research uses a qualitative research approach with a phenomenology type of study. Data collection techniques employed are observation, interviews, and documentation. The data analysis techniques used are data reduction, data display, and conclusion drawing. The data validity techniques used are triangulation and member checking. Research Findings The results of this research show that 1. The full-day school system at SDS IT Sulthoniyah Sambas is divided into two parts: extracurricular and intracurricular. Extracurricular activities include: 1) scouting; and 2) karate. Intracurricular activities include: 1) BTQ (Reading and Writing the Quran); 2) worship practice; 3) salam (greeting) culture; and 4) culture of reading selected short surahs (from the Quran). 2.  The obstacles to the full-day school system at SDS IT Sambas are: 1) facilities and infrastructure; 2) creating lesson plans that adapt to curriculum changes; 3) consistency and optimization of services to students' parents. Meanwhile, the opportunities for the full-day school system at SDS IT Sulthoniyah Sambas are: 1) learning that aligns with students' needs and potential; 2) enrichment of students' experiences in daily life; and 3) obtaining quality education. 3. The implications of the full-day school system on student development at SDS IT Sulthoniyah Sambas are: 1) the development of students' cognitive, affective, and psychomotor domains; 2) students' background; 3) interaction with the environment; 4) relevant learning; 5) external threats at school; 6) emotional development; and 7) moral development.